Pengendalian Internal dan Good Corporate Governance: Upaya Pencegahan Fraud pada Perumda BPR Majalengka - Krisniawan, Hendra; Mutaqin, Muhammad Ilham Sukma; Khoerulloh, Abd. Kholik (Brainy: Jurnal Riset Mahasiswa, 2023)
Fraud is a serious threat that can harm financial institutions such as Perumda BPR Majalengka. Fraud can appear in various forms, ranging from financial manipulation to acts of abuse of authority. This study aims to determine the extent to which internal control and good corporate governance can prevent fraud at Perumda BPR Majalengka. This study uses a descriptive method with a quantitative approach. The sample used in this study were 80 employees of Perumda BPR Majalengka. The results of this study indicate that internal control and good corporate governance have a significant positive effect on fraud prevention with a value of Fcount > Ftable (601.283 > 3.11) and a significant level of 0.000 or below the probability value of 0.05 (0.000 < 0.05). This study provides a clear view to company management regarding the importance of integration between effective internal control and the implementation of good corporate governance principles in fraud prevention efforts. They can use these findings as a foundation to develop stronger strategies in risk management and improve the overall integrity of the company.